MODERN EXAMINATION METHODS AND PRINCIPLES OF TREATMENT OF ACUTE SINUSITIS DISEASES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, special attention is paid to clarifying the signs observed in acute and chronic inflammation of the nasal cavity, important diagnostic factors in diagnosis and modern principles of treatment.